Peran Pelatihan Public Speaking Dalam Menumbuhkan Rasa Percaya Diri Siswa - Ambarsari, Dewi; Putri, Martina Shalaty (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Communication is a key factor in the effective delivery of messages. Therefore,every individual must possess the ability to communicate effectively and efficiently.Public speaking is one form of effective communication that requires specificskills. A lack of communication skills can hinder an individual's confidence whenspeaking in public. Public speaking is often called